2023
DOI: 10.3390/cells12070998
|View full text |Cite
|
Sign up to set email alerts
|

Rejuvenation of Mesenchymal Stem Cells to Ameliorate Skeletal Aging

Abstract: Advanced age is a shared risk factor for many chronic and debilitating skeletal diseases including osteoporosis and periodontitis. Mesenchymal stem cells develop various aging phenotypes including the onset of senescence, intrinsic loss of regenerative potential and exacerbation of inflammatory microenvironment via secretory factors. This review elaborates on the emerging concepts on the molecular and epigenetic mechanisms of MSC senescence, such as the accumulation of oxidative stress, DNA damage and mitochon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 204 publications
1
2
0
Order By: Relevance
“…This method provided a simple, effective and low-cost but specific approach to directly visualise the lineage choice of osteogenesis and adipogenesis of BMSCs. Moreover, our results not only confirmed that cultured young BMSCs were closer to osteoblasts than adipocytes[5], but also verified that aged BMSCs preferentially differentiation into adipocytes instead of osteoblasts[1, 2, 13]. However, whether the doses of supplemental drugs that were used to induce BMSCs differentiation are optimization combination still needed further studies.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…This method provided a simple, effective and low-cost but specific approach to directly visualise the lineage choice of osteogenesis and adipogenesis of BMSCs. Moreover, our results not only confirmed that cultured young BMSCs were closer to osteoblasts than adipocytes[5], but also verified that aged BMSCs preferentially differentiation into adipocytes instead of osteoblasts[1, 2, 13]. However, whether the doses of supplemental drugs that were used to induce BMSCs differentiation are optimization combination still needed further studies.…”
Section: Discussionsupporting
confidence: 72%
“…It is widely accepted that aged BMSCs have decreased abilities to be differentiated into osteoblasts and increased abilities to be adipocytes [1,13]. In this study, we also used the OA medium to investigate its effects on aged BMSCs.…”
Section: Resultsmentioning
confidence: 99%
“…It is widely accepted that aged BMSCs have decreased abilities to be differentiated into osteoblasts and increased abilities to be adipocytes [ 1 , 13 ]. In this section, we also used the OA medium to investigate its effects on aged BMSCs.…”
Section: Methods Detailsmentioning
confidence: 99%